Optimization of the Design of Cycle Networks: Application in the City of Rio de Janeiro - (:unkn) unknown (LACCEI, 2024)
Cycling networks are an attractive and important factor for the use of bicycles as a means of transport. These networks consist of bike routes, which can be separated from motorized traffic or not. The goal of the cycling network is to connect cyclists' ...
Keywords: Redes ciclistas; Optimización